2016
DOI: 10.1002/cam4.590
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial ovarian cancer subtypes attributable to smoking in the Norwegian Women and Cancer Study, 2012

Abstract: Among European women, ovarian cancer is the fifth most common cancer. Smoking is an established risk factor for mucinous tumors. We estimated the impact of smoking in Norwegian women using population attributable fractions (PAFs) of epithelial ovarian cancer (EOC), by invasiveness and by histological subtypes in the Norwegian Women and Cancer Study with an average of 13.2 years of follow‐up. During >2 million person‐years, a total of 915 incident EOC cases, of which 667 (73%) invasive and 248 (27%) borderline,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 22 publications
0
8
0
1
Order By: Relevance
“…Seven cohort studies presented results on overall ovarian cancer risk (21)(22)(23)(24)(25)(26)32). Among them only one reported an increased risk associated with current smoking (HR ¼ 1.4; 95% CI, 1.0-1.8), when borderline and invasive cases were combined (25).…”
Section: Resultsmentioning
confidence: 99%
“…Seven cohort studies presented results on overall ovarian cancer risk (21)(22)(23)(24)(25)(26)32). Among them only one reported an increased risk associated with current smoking (HR ¼ 1.4; 95% CI, 1.0-1.8), when borderline and invasive cases were combined (25).…”
Section: Resultsmentioning
confidence: 99%
“…The few prospective cohort studies that have investigated the association between measure of smoking exposure and the risk of subtypes of OC (Tworoger et al , 2008; Gram et al , 2012; Licaj et al , 2016) found no association between smoking duration and mucinous OCs. Each 20 additional pack-years in ever compared with never smokers was associated with a significant 20% higher risk of invasive mucinous OC (Wentzensen et al , 2016).…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study (Wentzensen et al , 2016), number of pack-years, which was the only measure of smoking exposure studied, was associated with a higher risk of invasive mucinous OC among ever smokers. Two reports from the same study population found a positive association between number of cigarettes smoked per day, smoking duration in years, and the risk of borderline OC (Gram et al , 2008; Licaj et al , 2016). One reason for the variation in these results may be the different methods employed to assess and analyse these measures of smoking exposure.…”
mentioning
confidence: 81%
See 1 more Smart Citation
“…Adiposity increases the risk of uterine carcinoma but is less associated with ovarian carcinoma . Smoking is associated with lower risk of uterine carcinoma but not with overall risk of ovarian carcinoma . Several studies have compared risk estimates for subtypes of uterine or ovarian carcinoma to determine if they have different risk factors .…”
mentioning
confidence: 99%